Perceptions of public on justice: a socio-legal analysis of influencing factors - Kaushal, Swati; Shrivastava, Vikalp; Sahil, Gurudev; Yadav, Pratishtha (Ius Humani. Jornal do direito, 2025)
Public plays a vital part in the administration of justice in a representative society. The role of public to accomplish its accountabilities is also vital for the society to function proficiently. In that sense, to build and sustain confidence of the public, it is relevant to institute congruence of the public opinion and justice administration and its workability. Many aspects are responsible for the perception of crime by the public: socio-economic dynamics; demographic aspects like race, gender, personal beliefs and attitudes; religious orientations; etc. It is also pragmatic that age shows a significant part in varying dynamics of crime and punishment for people. Older age people have been found to favor stern punishments of imprisonment, but the younger are more inclined towards reformatory initiatives. Therefore, policy makers should focus on ameliorating the wrongdoer than putting them behind prison as they are also a member of the society. In other words, they must be rehabilitated by vigorous reformatory processes of the system to reintegrate with the public and to avoid recidivism, which will confirm law and order and prevent future crimes. The paper attempts to analyze and understand various aspects which affect the equilibrium of crime and punishment and its perceptions by the public; regarding this, various aspects that contribute to frame public perception are media, political influence, socio-economic disparities, gender-based perception, attitude of police and cultural narratives; these are all explored. Finally, the paper concludes with suggestions for the improvement of public opinion.